Optimal cooling of a driven artificial atom in dissipative environment - Du, Lingjie; Yu, Yang; Lan, Dong (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We study microwave-driven cooling in a superconducting flux qubit subjected to environment noises. For the weak decoherence, our analytical results agree well with the experimental observations and show that the microwave amplitude for optimal cooling should depend linearly on the dc flux detuning. With the decoherence stronger, more vibrational degrees of freedom (analogous with atomic physics) couple in, making the ordinary cooling method less effective or even fail. We propose an improved cooling method, which can eliminate the perturbation of additional vibrational degrees of freedom hence keep high efficiency, even under the strong decoherence. Furthermore, we point out that the decoherence can tune the frequency where microwave-driven Landau–Zener transition reaches maximum, displaying the feature of incoherent dynamics which is important for the optimal cooling of qubits and other quantum systems.